1993
DOI: 10.1159/000108723
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Segmental Dilatation of the Anterior Cerebral Artery

Abstract: We report 3 patients with anterior cerebral artery (ACA) territory infarction, angiograms of whom demonstrated segmental dilatation of the homolateral A2 portion with no other abnormality at the acute phase. The dilatatory changes were found to have disappeared, when angiography was repeated 1–6 years after infarction. A reversible segmental dilatation of the ACA may be an important cause of ACA territory infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The other 3 had A2 segments which were initially dilated and then later restored to a normal state. As vascular changes in these cases were restricted to the ACA, and resolution of stenosis or occlusion has been considered a reliable angiographic sign of arterial dissection, they concluded that diagnoses of isolated ACA dissection seemed reasonable [11] . Our case presented a defi nite diagnosis, because the double lumen sign was demonstrated using 3D-RA.…”
Section: Discussionmentioning
confidence: 97%
“…The other 3 had A2 segments which were initially dilated and then later restored to a normal state. As vascular changes in these cases were restricted to the ACA, and resolution of stenosis or occlusion has been considered a reliable angiographic sign of arterial dissection, they concluded that diagnoses of isolated ACA dissection seemed reasonable [11] . Our case presented a defi nite diagnosis, because the double lumen sign was demonstrated using 3D-RA.…”
Section: Discussionmentioning
confidence: 97%
“…Although the mechanisms remain unknown, the most likely etiologies are considered to be "reversible cerebral segmental vasoconstriction and dilatation," described by Call et al, 14 and isolated ACA dissections. 15 Reversible arterial lesions confined to the ACA may be important causes of ACA territory infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral infarcts localized in the anterior cerebral artery (ACA) territory are relatively rare, representing 0.5– 3% of all ischemic strokes [1,2,3,4,5,6]. Large artery atherosclerosis is the leading etiology of ACA territory infarction [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…All of these 3 patients were relatively young, had headache, and no previous history of stroke. For them, arterial dissection was regarded as the most plausible mechanism, but conclusive evidence was not obtained [6]. Several years afterwards, we succeeded in visualizing the pathognomonic findings of dissection, including the double lumen sign using 3-dimensional rotational angiography (3D-RA), which were not evident on MRA or conventional digital subtraction angiography (DSA) [7].…”
Section: Introductionmentioning
confidence: 99%